Welfare Implications of Personalized Pricing in Competitive Platform Markets: The Role of Network Effects - Qiuyu Lu; Noriaki Matsushima; Shiva Shekhar (Center for Economic Studies and ifo Institute (CESifo), 2024)
This study explores the welfare impact of personalized pricing for consumers in a duopolistic two-sided market, with consumers single-homing and developers affiliating with a platform according to their outside option. Personalized pricing, which is private in nature, cannot influence expectations regarding the network sizes, inducing the platforms to offer lower participation fees for developers. Those lower fees increase network benefits for consumers, allowing the platforms to exploit these benefits through personalized pricing. Personalized prices are higher when the network value for developers is high, benefiting competing platforms at the expense of consumers. These findings offer policy insights on personalized pricing.
Keywords: L13; D43; 330; personalized pricing; uniform prices; two-sided market; content developers